Inheritance of Early Maturity in Some Cowpea (Vigna unguiculata (L.) Walp.) Genotypes under Rain Fed Conditions in Northern Ghana. (28th March 2018) - Owusu, Emmanuel Yaw; Akromah, Richard; Denwar, Nicholas Ninju; Adjebeng-Danquah, Joseph; Kusi, Francis; Haruna, Mohammed
Abstract : A field experiment was conducted at Savanna Agricultural Research Institute in 2015 cropping season to examine the inheritance of early maturity among an extra-early maturing landrace Sanzi and a medium maturing variety Padi-Tuya and their progenies. The results indicated highly significant (P < 0.01 ) genetic variations for the maturity indices, namely, days to first flower initiation (DFFI), days to 50% flowering (DFF), days to first pod maturity (DFPM), days to 90% pod maturity (DNPM), and plant height (P_PLT), seed per pod (S_Pod), and hundred seed weight (H_SWT). Heritability estimates for these traits varied from 74% to 99%. No significant differences (P > 0.05 ) were observed between F1 and RF1, implying absence of maternal effect. The segregation ratio in the F2 population for early and medium maturity fitted into the ratio 3 : 1, indicating single dominant gene mode of inheritance. Significant positive correlations were found between DNPM, DFFI, DFF, and DFPM; hence selection criteria to improve early maturity of cowpea should focus on these traits. Grain yield also had significant positive correlations with maturity indices indicating high grain yield is associated with late maturity; therefore, high grain yield should be considered alongside early maturity when selecting progenies for earliness.